Histomorphological comparisons in testicles between Barb horse, donkey and mule - Derouiche, Louiza; Houssou, Hind; Zatra, Yamina; Boussaidane, Bahia; Sayahoui, Hajer; Ouennes, Houria (Acta Scientiarum. Animal Sciences, 2023)
The mule is a sterile hybrid domestic animal that results from the breeding of a male donkey with a female horse, understanding the reproductive biology of these species is very critical. The goal of this paper was to perform a comparative and more accurate histomorphometric of the testicles in Barb horse, donkeys and mules. Microscopic examinations and histological description were carried on genital tract of horses, donkeys and mules healthy and mature; this study was conducted during April-May 2018. The histological and the morphological results shows a similarity between the two equine species and the infertile hybrid for the testicles, the epididymis and the vas deferens. However, the difference was presented on the morphometric data; vas deferens was more voluminous in the horse and donkey than a mule. Moreover, the differences were significantly higher for the surface of the seminiferous tubules and for the epididymis. The lumen of the seminiferous tubules in mule was significantly higher than in the horse and donkey. Absence of gametes in the epididymal cavity and lower number of gametes in the mule. Furthermore, we have noted the presence of spermatozoa in one mule 16.67%. Therefore, the mule could complete development of spermatogenesis.